Indian monsoon regulates the sediment supply of the Upper Yangtze River since ∼2 Ma - Xudong Zhao; Taylor F. Schildgen; Huiping Zhang; Weitao Wang; Yan Ma; Ping Wang; Yarong Zhang; Yifei Li; Chaopeng Li; Hongseng Xie; Peizhen Zhang (Earth and Planetary Science Letters, 2026)

Settling by water: Human habitation adapted to landscape evolution at the Xuecheng site in the lower reaches of the Yangtze River during the Mid-late Holocene - Zhiping Zhang; Zhujun Hu; Xingyu Zhou; Hui Peng; Jue Sun; Jiahao Xu; Hongwei Shi; Lin Yang; Ping Zhang; Feng Xu; Harry F. Lee; Xin Jia (Science China Earth Sciences, 2026)

New linear bromopyrrole-imidazolidine alkaloids from the Formosan sponge Agelas nakamurai - You-Cheng Lin; Atallah F. Ahmed; Chung-Wei Fu; Shu-Fen Chiou; Hui-Chun Wang; Ping-Jyun Sung; Jyh-Horng Sheu (Natural Product Research, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Proteome-wide reverse molecular docking reveals folate receptor as a mediator of PFAS-induced neurodevelopmental toxicity - Ally Xinyi Kong; Maja Johnson; Jinhua Chi; Aiden F. Eno; Khoa Pham; Ping Zhang; Haiwei Gu; Yijie Geng (Journal of Hazardous Materials, 2026)

Impact of dispersion correction in DFT-enhanced anisotropic NMR for stereochemical elucidation of flexible marine natural products - Lu-Ping Chi; Xiao-Lu Li; Anton F. Ketzel; Armando Navarro-Vázquez; Caspar J. Schattenberg; Xiao-Ming Li; Xin Li; Han Sun; Bin-Gui Wang (Marine Life Science & Technology, 2025)
Although anisotropic NMR spectroscopy has emerged as a powerful method for determining the relative configuration of complex natural products, major challenges persist with structurally flexible molecules. In this study, we conducted a systematic comparative analysis of stereochemical elucidation, combining anisotropic NMR spectroscopy and density functional theory (DFT) calculations on spiroepicoccin B ( 1 ) and epicoccin V ( 2 ), which were characterized as thiodiketopiperazine marine natural products isolated from the deep-sea-derived fungus Epicoccum nigrum SD-388. For the flexible compound 2 , we compared various conformational sampling approaches, including an assessment of the quality of relative energies within the obtained ensembles. We demonstrated the critical role of dispersion correction within DFT computations to precisely account for weak non-bonded intramolecular interactions. By integrating anisotropic NMR analysis, chemical shifts, electronic circular dichroism, and DFT computations, we determined the absolute configurations and conformational ensembles for 1 and 2 , respectively, highlighting the significance of the intramolecular methyl–π interaction in stabilizing one of the conformers. Our study introduces new strategies to address conformational flexibility in the stereochemical elucidation of challenging organic molecules.

Deletion of the Transient Receptor Potential Melastatin 2 Gene Mitigates the 6-Hydroxydopamine-Induced Parkinson’s Disease–Like Pathology - Ana Flavia F. Ferreira; Henning Ulrich; Yasuo Mori; Zhong-Ping Feng; Hong-Shuo Sun; Luiz Roberto Britto (Molecular Neurobiology, 2025)

Biosynthesized silver nanoparticles mitigate charcoal rot and root-knot nematode disease complex in faba bean - Alyaa Nasr; Ahmed Fathy Yousef; Mohamed G.A. Hegazy; Mohammed A. Abdel-Mageed; Ezzat H. Elshazly; Mahmoud Gad; Sobhi F. Lamlom; Islam I. Teiba; Gamal A. Gouda; Waleed M. Ali; Ahmed A.S. Abd-Elraheem; Asmaa El-Nagar; et al. (Physiological and Molecular Plant Pathology, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Mesozoic crustal growth and recycling along the Southern margin of Eurasia: Magmatic rocks from the Sanandaj-Sirjan Zone of Iran - Hadi Shafaii Moghadam; Wenjiao Xiao; William L. Griffin; Ghasem Ghorbani; Qiu-li Li; Orhan Karsli; Jose F. Santos; Xianquan Ping; Marzieh Bayati; Suzanne Y. O'Reilly (Lithos, 2024)

A field trial for remediation of multi-metal contaminated soils using the combination of fly ash stabilization and Zanthoxylum bungeanum- Lolium perenne intercropping system - Han Zhang; Xiaoyong Lv; Zhaowen Yang; Qian Li; Ping Wang; Shuqiang Zhang; Yaqiong Xu; Xuejia Wang; Esmat F. Ali; Peter S. Hooda; Sang Soo Lee; Ronghua Li; et al. (Journal of Environmental Management, 2024)

Correction: The Microphytobenthos are Abundant and Mediate Key Carbon Fluxes in Tropical Mangroves - Yan Ping Loo; Xiaoguang Ouyang; Derrick Y. F. Lai; Shing Yip Lee (Estuaries and Coasts, 2024)

The Microphytobenthos are Abundant and Mediate Key Carbon Fluxes in Tropical Mangroves - Yan Ping Loo; Xiaoguang Ouyang; Derrick Y. F. Lai; Shing Yip Lee (Estuaries and Coasts, 2024)
The microphytobenthos (MPB) are known to play important ecological roles in estuarine ecosystems. While tidal flat MPB are widely studied, mangrove MPB are often overlooked due to the common belief that the light-limited environment under the mangrove canopy is not conducive to MPB growth. We assessed the biomass and community characteristics of the MPB in two contrasting mangrove forests (silty substrate and brackish influence versus sandy substrate and oceanic influence), their seasonal photosynthetic performance, as well as their role in mediating porewater carbon flux. Biomass measured as chlorophyll a concentration indicated that MPB abundance was equal, if not higher, in mangroves than on tidal flats. While mangrove sediments fostered an equally rich assemblage of MPB (estimated 23 to 45 genera) as the adjacent tidal flat, the MPB genus composition was different across all habitats, sites, and seasons, indicating the strong environmental influence on MPB assemblages. This study identified porewater salinity, temperature, and pH, as well as irradiance level and surface soil temperature to be accountable for 23.5% of this variation. MPB in all sampling locations were dominated by pennate diatoms, while cyanobacteria were common in the estuarine (as opposed to oceanic) site. Compared to tidal flat MPB, mangrove MPB exhibited photosynthetic performance characteristic of lower light acclimation. A mesocosm experiment using enriched stable isotopes of carbon and nitrogen indicated that a tight coupling exists between mangrove-derived carbon and MPB. Mangrove MPB are abundant and different from tidal flat MPB, and are functional photosynthetic entities with a regulatory role in nutrient cycling in mangrove ecosystems.

Polyrate 2023: A computer program for the calculation of chemical reaction rates for polyatomics. New version announcement - Rubén Meana-Pañeda; Jingjing Zheng; Junwei Lucas Bao; Shuxia Zhang; Benjamin J. Lynch; José C. Corchado; Yao-Yuan Chuang; Patton L. Fast; Wei-Ping Hu; Yi-Ping Liu; Gillian C. Lynch; Kiet A. Nguyen; et al. (Computer Physics Communications, 2024)

Hydrodynamic response to bathymetric changes in Tampa Bay, Florida - Jing Chen; Yonggang Liu; Robert H. Weisberg; Steven A. Murawski; Sherryl Gilbert; David F. Naar; Lianyuan Zheng; Matthew Hommeyer; Catherine Dietrick; Mark E. Luther; Cheryl Hapke; Edward Myers; et al. (Deep Sea Research Part II: Topical Studies in Oceanography, 2023)

Interfacial adsorption of gold nanoparticles on arsenian pyrite: New insights for the transport and deposition of gold nanoparticles - Xin Nie; Quan Wan; Michael F. Hochella; Suxing Luo; Meizhi Yang; Shanshan Li; Yuhong Fu; Ping Zeng; Zonghua Qin; Wenbin Yu (Chemical Geology, 2023)

Evaluating drought monitoring utility of the top-down and bottom-up satellite precipitation products over mainland China from a three-dimensional perspective - Yuefen Zhang; Chuanhao Wu; Pat J.-F. Yeh; Jianzhu Li; Jiayun Li; Bill X. Hu; Ping Feng (Journal of Hydrology, 2023)

Chlorpyrifos fate in the Arctic: Importance of analyte structure in interactions with Arctic dissolved organic matter - Lauren E. O'Connor; Pippin Robison; Ginna Quesada; Jill F. Kerrigan; Robyn C. O'Halloran; Jennifer J. Guerard; Yu-Ping Chin (Water Research, 2023)

Responses of coastal sediment organic and inorganic carbon to habitat modification across a wide latitudinal range in southeastern China - Yan Hong; Linhai Zhang; Ping Yang; Chuan Tong; Yongxin Lin; Derrick Y. F. Lai; Hong Yang; Yalian Tian; Wanyi Zhu; Kam W. Tang (CATENA, 2023)

Tailorable carbon cloth electrodes covered with heterostructured Co/CoO/CoN interfaces for scalable electrocatalytic overall water splitting - Wei Zhang; Cong Li; Jun-Yang Ji; Zheng Niu; Hongwei Gu; Brendan F. Abrahams; Jian-Ping Lang (Chemical Engineering Journal, 2023)

The loss of cardiac SIRT3 decreases metabolic flexibility and proteostasis in an age-dependent manner - Ping Li; Maria F. Newhardt; Satoshi Matsuzaki; Craig Eyster; Atul Pranay; Frederick F. Peelor; Albert Batushansky; Caroline Kinter; Kumar Subramani; Sandeep Subrahmanian; Jasimuddin Ahamed; Pengchun Yu; et al. (GeroScience, 2023)
SIRT3 is a longevity factor that acts as the primary deacetylase in mitochondria. Although ubiquitously expressed, previous global SIRT3 knockout studies have shown primarily a cardiac-specific phenotype. Here, we sought to determine how specifically knocking out SIRT3 in cardiomyocytes (SIRTcKO mice) temporally affects cardiac function and metabolism. Mice displayed an age-dependent increase in cardiac pathology, with 10-month-old mice exhibiting significant loss of systolic function, hypertrophy, and fibrosis. While mitochondrial function was maintained at 10 months, proteomics and metabolic phenotyping indicated SIRT3 hearts had increased reliance on glucose as an energy substrate. Additionally, there was a significant increase in branched-chain amino acids in SIRT3cKO hearts without concurrent increases in mTOR activity. Heavy water labeling experiments demonstrated that, by 3 months of age, there was an increase in protein synthesis that promoted hypertrophic growth with a potential loss of proteostasis in SIRT3cKO hearts. Cumulatively, these data show that the cardiomyocyte-specific loss of SIRT3 results in severe pathology with an accelerated aging phenotype.

Hypoxia-Induced Neurite Outgrowth Involves Regulation Through TRPM7 - Ekaterina Turlova; Delphine Ji; Marielle Deurloo; Raymond Wong; Andrea Fleig; F. David Horgen; Hong-Shuo Sun; Zhong-Ping Feng (Molecular Neurobiology, 2023)

Corrigendum to “Comparative efficacy of omega-3 polyunsaturated fatty acids on major cardiovascular events: A network meta-analysis of randomized controlled trials” [Progress in Lipid Research. 2022 Oct 28;88:101196. doi: 10.1016/j.plipres.2022.101196] - Bo Yang; Ping-Tao Tseng; Xiang Hu; Bing-Yan Zeng; Jane Pei-Chen Chang; Yang Liu; Wei-Jie Chu; Shuang-Shuang Zhang; Zhi-Liang Zhou; Chih-Sheng Chu; Cheng-Ho Chang; Yu-Kang Tu; et al. (Progress in Lipid Research, 2023)

Modelling the impacts of inhibitors and fertilizer placement on maize yield and ammonia, nitrous oxide and nitrate leaching losses in southwestern Ontario, Canada - Rong Jiang; Jingyi Yang; Craig F. Drury; Brian B. Grant; Ward N. Smith; Wentian He; Daniel W. Reynolds; Ping He (Journal of Cleaner Production, 2023)

Lactic acid bacteria promoted soil quality and enhanced phytoextraction of Cd and Zn by mustard: A trial for bioengineering of toxic metal contaminated mining soils - Shuqiang Zhang; Yiman Li; Ping Wang; Han Zhang; Esmat F. Ali; Ronghua Li; Sabry M. Shaheen; Zengqiang Zhang (Environmental Research, 2023)

Genetic analysis of North American Phragmites australis guides management approaches - Denise L. Lindsay; Joanna Freeland; Ping Gong; Xin Guan; Nathan E. Harms; Kurt P. Kowalski; Richard F. Lance; Dong-Ha Oh; Bradley T. Sartain; Douglas L. Wendell (Aquatic Botany, 2023)

A systematic review and meta-analysis of non-vitamin K antagonist oral anticoagulants vs vitamin K antagonists after transcatheter aortic valve replacement in patients with atrial fibrillation - Amanda Jia Qi Ooi; Chloe Wong; Timothy Wei Ern Tan; Trina Priscilla Ng; Yao Neng Teo; Yao Hao Teo; Nicholas L. Syn; Andie H. Djohan; Yinghao Lim; Leonard L. L. Yeo; Benjamin Y. Q. Tan; Mark Yan-Yee Chan; et al. (European Journal of Clinical Pharmacology, 2022)

Global evaluation of inhibitor impacts on ammonia and nitrous oxide emissions from agricultural soils: A meta‐analysis - Daijia Fan; Wentian He; Ward N. Smith; Craig F. Drury; Rong Jiang; Brian B. Grant; Yaoyao Shi; Daping Song; Yanhua Chen; Xuexia Wang; Ping He; Guoyuan Zou (Global Change Biology, 2022)
Inhibitors are widely considered an efficient tool for reducing nitrogen (N) loss and improving N use efficiency, but their effectiveness is highly variable across agroecosystems. In this study, we synthesized 182 studies (222 sites) worldwide to evaluate the impacts of inhibitors (urease inhibitors [UI], nitrification inhibitors [NI] and combined inhibitors) on crop yields and gaseous N loss (ammonia [NH 3 ] and nitrous oxide [N 2 O] emissions) and explored their responses to different management and environmental factors including inhibitor application timing, fertilization regime, cropping system, water management, soil properties and climatic conditions using subgroup meta‐analysis, meta‐regression and multivariate analyses. The UI were most effective in enhancing crop yields (by 5%) and reducing NH 3 volatilization (by 51%), whereas NI were most effective at reducing N 2 O emissions (by 49%). The application of UI mitigates NH 3 loss and increases crop yields especially in high NH 3 ‐N loss scenarios, whereas NI application would minimize the net N 2 O emissions and the resultant environmental impacts especially in low NH 3 ‐N loss scenarios. Alternatively, the combined application of UI and NI enables producers to balance crop production and environmental conservation goals without pollution tradeoffs. The inhibitor efficacy for decreasing gaseous N loss was dependent upon soil and climatic conditions and management practices. Notably, both meta‐regression and multivariate analyses suggest that inhibitors provide a greater opportunity for reducing fertilizer N inputs in high‐N‐surplus systems and presumably favor crop yield enhancement under soil N deficiency situations. The pursuit of an improved understanding of the interactions between plant‐soil‐climate‐management systems and different types of inhibitors should continue to optimize the effectiveness of inhibitors for reducing environmental losses while increasing productivity.

A20 attenuates pyroptosis and apoptosis in nucleus pulposus cells via promoting mitophagy and stabilizing mitochondrial dynamics - Xin Peng; Cong Zhang; Zhi-Min Zhou; Kun Wang; Jia-Wei Gao; Zhan-Yang Qian; Jun-Ping Bao; Hang-Yu Ji; V. L. F. Cabral; Xiao-Tao Wu (Inflammation Research, 2022)

Bridge to the future: Important lessons from 20 years of ecosystem observations made by the OzFlux network - Jason Beringer; Caitlin E. Moore; Jamie Cleverly; David I. Campbell; Helen Cleugh; Martin G. De Kauwe; Miko U. F. Kirschbaum; Anne Griebel; Sam Grover; Alfredo Huete; Lindsay B. Hutley; Johannes Laubach; et al. (Global Change Biology, 2022)
In 2020, the Australian and New Zealand flux research and monitoring network, OzFlux, celebrated its 20 th anniversary by reflecting on the lessons learned through two decades of ecosystem studies on global change biology. OzFlux is a network not only for ecosystem researchers, but also for those ‘next users’ of the knowledge, information and data that such networks provide. Here, we focus on eight lessons across topics of climate change and variability, disturbance and resilience, drought and heat stress and synergies with remote sensing and modelling. In distilling the key lessons learned, we also identify where further research is needed to fill knowledge gaps and improve the utility and relevance of the outputs from OzFlux. Extreme climate variability across Australia and New Zealand (droughts and flooding rains) provides a natural laboratory for a global understanding of ecosystems in this time of accelerating climate change. As evidence of worsening global fire risk emerges, the natural ability of these ecosystems to recover from disturbances, such as fire and cyclones, provides lessons on adaptation and resilience to disturbance. Drought and heatwaves are common occurrences across large parts of the region and can tip an ecosystem's carbon budget from a net CO 2 sink to a net CO 2 source. Despite such responses to stress, ecosystems at OzFlux sites show their resilience to climate variability by rapidly pivoting back to a strong carbon sink upon the return of favourable conditions. Located in under‐represented areas, OzFlux data have the potential for reducing uncertainties in global remote sensing products, and these data provide several opportunities to develop new theories and improve our ecosystem models. The accumulated impacts of these lessons over the last 20 years highlights the value of long‐term flux observations for natural and managed systems. A future vision for OzFlux includes ongoing and newly developed synergies with ecophysiologists, ecologists, geologists, remote sensors and modellers.

Impact of Different Wind Representations on Resonant Ocean Near-inertial Motions in the Gulf of Mexico - Chuan-Yuan Hsu; Jongsun Kim; Ping Chang; Steven F. DiMarco (Ocean Science Journal, 2022)

Earth’s Rotation: Observations and Relation to Deep Interior - Jérémy Rekier; Benjamin F. Chao; Jianli Chen; Véronique Dehant; Séverine Rosat; Ping Zhu (Surveys in Geophysics, 2022)

Associations of Blood Pressure and Carotid Flow Velocity with Brain Volume and Cerebral Small Vessel Disease in a Community-Based Population - Shao-Yuan Chuang; Pei-Ning Wang; Liang-Kung Chen; Kun-Hsien Chou; Chih-Ping Chung; Chen-Huan Chen; Gary F. Mitchell; Wen-Harn Pan; Hao-Min Cheng (Translational Stroke Research, 2021)

TRPM7 Mediates Neuronal Cell Death Upstream of Calcium/Calmodulin-Dependent Protein Kinase II and Calcineurin Mechanism in Neonatal Hypoxic-Ischemic Brain Injury - Ekaterina Turlova; Raymond Wong; Baofeng Xu; Feiya Li; Lida Du; Steven Habbous; F. David Horgen; Andrea Fleig; Zhong-Ping Feng; Hong-Shuo Sun (Translational Stroke Research, 2021)

Field cage assessment of feeding damage by Halyomorpha halys on kiwifruit orchards in China - Ju-Hong Chen; Gonzalo A. Avila; Feng Zhang; Lindy F. Guo; Manoharie Sandanayaka; Qian-Qian Mi; Shu-Sen Shi; Jin-Ping Zhang (Journal of Pest Science, 2020)

Temporal profile of illicit drug consumption in Guangzhou, China monitored by wastewater-based epidemiology - Xiaohan Zhang; Riheng Huang; Ping Li; Yuan Ren; Jianfa Gao; Jochen F. Mueller; Phong K Thai (Environmental Science and Pollution Research, 2019)

Production and uptake of dissolved carbon, nitrogen, and phosphorus in overlying water of aquaculture shrimp ponds in subtropical estuaries, China - Ping Yang; Hong Yang; Derrick Y. F. Lai; Baoshi Jin; Chuan Tong (Environmental Science and Pollution Research, 2019)

Conserved peptides enhance immune efficiency of inactive vaccines against emerging avian influenza viruses in chicken - Jin Xiao; Lei Zhang; Zhenbao Wang; Wangzhen Xiang; Ping Lu; Yingze Zhao; Min Han; Airong Ma; Peng Qi; Ming Wang; George F. Gao; William J. Liu (Science China Life Sciences, 2017)

Data assimilation method for fractured reservoirs using mimetic finite differences and ensemble Kalman filter - Jing Ping; Omar Al-Hinai; Mary F. Wheeler (Computational Geosciences, 2017)

Erratum to: CX3CR1 deficiency accelerates the development of retinopathy in a rodent model of type 1 diabetes - Eleni Beli; James M. Dominguez; Ping Hu; Jeffrey S. Thinschmidt; Sergio Caballero; Sergio Li Calzi; Defang Luo; Sumathi Shanmugam; Tatiana E. Salazar; Yaqian Duan; Michael E. Boulton; Susanna Mohr; et al. (Journal of Molecular Medicine, 2017)

Assessment of ecological instream flow requirements under climate change Pseudorasbora parva - Q. Liu; H. Yu; L. Liang; F. Ping; X. Xia; X. Mou; J. Liang (International Journal of Environmental Science and Technology, 2017)

Morphogenesis and Gene Mapping of deformed interior floral organ 1 (difo1), a Novel Mutant Associated with Floral Organ Development in Rice - Lianping P. Sun; Yingxin X. Zhang; Peipei P. Zhang; Zhengfu F. Yang; Xiaoxiao X. Zhou; Dandan D. Xuan; Md Habibur H. Rahman; Zihe H. Li; Weixun X. Wu; Xiaodeng D. Zhan; Xihong H. Shen; Ping Yu; et al. (Plant Molecular Biology Reporter, 2017)

Neuroprotective Effects of a PSD-95 Inhibitor in Neonatal Hypoxic-Ischemic Brain Injury - Baofeng Xu; Ai-Jiao Xiao; Wenliang Chen; Ekaterina Turlova; Rui Liu; Andrew Barszczyk; Christopher L. F. Sun; Ling Liu; Michael Tymianski; Zhong-Ping Feng; Hong-Shuo Sun (Molecular Neurobiology, 2016)

CX3CR1 deficiency accelerates the development of retinopathy in a rodent model of type 1 diabetes - Eleni Beli; James M. Dominguez; Ping Hu; Jeffrey S. Thinschmidt; Sergio Caballero; Sergio Li Calzi; Defang Luo; Sumathi Shanmugam; Tatiana E. Salazar; Yaqian Duan; Michael E. Boulton; Susanna Mohr; et al. (Journal of Molecular Medicine, 2016)

The Oldest Cranium of Sinomastodon (Proboscidea, Gomphotheriidae), Discovered in the Uppermost Miocene of Southwestern China: Implications for the Origin and Migration of This Taxon - Shi-Qi Wang; Xue-Ping Ji; Nina G. Jablonski; Denise F. Su; Jun-Yi Ge; Chang-Fen Ding; Teng-Song Yu; Wen-Qi Li; Jaroon Duangkrayom (Journal of Mammalian Evolution, 2016)

Bioactivity and chemical characterisation of Lophostemon suaveolens – an endemic Australian Aboriginal traditional medicinal plant - Tarannum Naz; Joanne Packer; Ping Yin; Joseph J. Brophy; Hans Wohlmuth; Dane E. Renshaw; Joshua Smith; Yaegl Community Elders; Subramanyam R. Vemulpad; Joanne F. Jamie (Natural Product Research, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

TRPM7 Regulates Axonal Outgrowth and Maturation of Primary Hippocampal Neurons - Ekaterina Turlova; Christine Y. J. Bae; Marielle Deurloo; Wenliang Chen; Andrew Barszczyk; F. David Horgen; Andrea Fleig; Zhong-Ping Feng; Hong-Shuo Sun (Molecular Neurobiology, 2016)

High-Performance Multiclass Classification Framework Using Cloud Computing Architecture - Feng-Sheng Lin; Chia-Ping Shen; Chia-Hung Liu; Han Lin; Chi-Ying F. Huang; Cheng-Yan Kao; Feipei Lai; Jeng-Wei Lin (Journal of Medical and Biological Engineering, 2015)

Differential requirements for H/ACA ribonucleoprotein components in cell proliferation and response to DNA damage - Ping Lin; Maral E. Mobasher; Yasaman Hakakian; Veena Kakarla; Anum F. Naseem; Heliya Ziai; Faizan Alawi (Histochemistry and Cell Biology, 2015)

cDNA cloning, expression, and immunolocalization of gonad-inhibiting hormone (GIH) in Litopenaeus vannamei - Guang-li Li; Si-ping Deng; Shu-na Jiang; Man Ye; Hua-pu Chen; Siuming F. Chan; Chun-hua Zhu (Genes & Genomics, 2015)

Genome-wide association study for refractive astigmatism reveals genetic co-determination with spherical equivalent refractive error: the CREAM consortium - Qing Li; Robert Wojciechowski; Claire L. Simpson; Pirro G. Hysi; Virginie J. M. Verhoeven; Mohammad Kamran Ikram; René Höhn; Veronique Vitart; Alex W. Hewitt; Konrad Oexle; Kari-Matti Mäkelä; Stuart MacGregor; et al. (Human Genetics, 2015)

The B″ regulatory subunit of protein phosphatase 2A mediates the dephosphorylation of rice retinoblastoma-related protein-1 - Edit Ábrahám; Ping Yu; Ilona Farkas; Zsuzsanna Darula; Erzsébet Varga; Noémi Lukács; Ferhan Ayaydin; Katalin F. Medzihradszky; Viktor Dombrádi; Dénes Dudits; Gábor V. Horváth (Plant Molecular Biology, 2015)

Satellite remote sensing of fine particulate matter (PM 2.5 ) air quality over Beijing using MODIS - Yangjie Guo; Nan Feng; Sundar A. Christopher; Ping Kang; F. Benjamin Zhan; Song Hong (International Journal of Remote Sensing, 2014)

Genome-wide association studies identified novel loci for non-high-density lipoprotein cholesterol and its postprandial lipemic response - Ping An; Robert J. Straka; Toni I. Pollin; Mary F. Feitosa; Mary K. Wojczynski; E. Warwick Daw; Jeffrey R. O’Connell; Quince Gibson; Kathleen A. Ryan; Paul N. Hopkins; Michael Y. Tsai; Chao-Qiang Lai; et al. (Human Genetics, 2014)

Expert assessment of vulnerability of permafrost carbon to climate change - E. A. G. Schuur; B. W. Abbott; W. B. Bowden; V. Brovkin; P. Camill; J. G. Canadell; J. P. Chanton; F. S. Chapin; T. R. Christensen; P. Ciais; B. T. Crosby; C. I. Czimczik; et al. (Climatic Change, 2013)

SH3GL2 is frequently deleted in non-small cell lung cancer and downregulates tumor growth by modulating EGFR signaling - Santanu Dasgupta; Jin Sung Jang; Chunbo Shao; Nitai D. Mukhopadhyay; Upneet K. Sokhi; Swadesh K. Das; Mariana Brait; Conover Talbot; Rex C. Yung; Shahnaz Begum; William H. Westra; Mohammad Obaidul Hoque; et al. (Journal of Molecular Medicine, 2013)

Fine mapping of 14q24.1 breast cancer susceptibility locus - Phoebe Lee; Yi-Ping Fu; Jonine D. Figueroa; Ludmila Prokunina-Olsson; Jesus Gonzalez-Bosquet; Peter Kraft; Zhaoming Wang; Kevin B. Jacobs; Meredith Yeager; Marie-Josèphe Horner; Susan E. Hankinson; Amy Hutchinson; et al. (Human Genetics, 2012)

Identification and mapping of conserved ortholog set (COS) II sequences of cacao and their conversion to SNP markers for marker-assisted selection in Theobroma cacao and comparative genomics studies - David N. Kuhn; Don Livingstone; Dorrie Main; Ping Zheng; Chris Saski; F. Alex Feltus; Keithanne Mockaitis; Andrew D. Farmer; Gregory D. May; Raymond J. Schnell; Juan C. Motamayor (Tree Genetics & Genomes, 2012)

Linked gene networks involved in nitrogen and carbon metabolism and levels of water-soluble carbohydrate accumulation in wheat stems - C. Lynne McIntyre; Rosanne E. Casu; Allan Rattey; M. Fernanda Dreccer; Jason W. Kam; Anthony F. van Herwaarden; Ray Shorter; Gang Ping Xue (Functional & Integrative Genomics, 2011)

Kinematics of the lumbar spine in elderly subjects with decreased bone mineral density - Heather Ting Ma; James F. Griffith; Zhengyi Yang; Anthony Wai Leung Kwok; Ping Chung Leung; Raymond Y. W. Lee (Medical & Biological Engineering & Computing, 2009)

A new method for determining lumbar spine motion using Bayesian belief network - Heather Ting Ma; Zhengyi Yang; James F. Griffith; Ping Chung Leung; Raymond Y. W. Lee (Medical & Biological Engineering & Computing, 2008)

Behavioral Response of Two Subterranean Termites (Isoptera: Rhinotermitidae) to Vibrational Stimuli - Xing Ping Hu; Arthur G. Appel; James F. A. Traniello (Journal of Insect Behavior, 2007)

Silencing the PTEN gene is protective against neuronal death induced by human immunodeficiency virus type 1 Tat - Tianyong Zhao; Mary H Adams; Shi-Ping Zou; Nazira El-Hage; Kurt F Hauser; Pamela E Knapp (Journal of NeuroVirology, 2007)

Donepezil primarily attenuates scopolamine-induced deficits in psychomotor function, with moderate effects on simple conditioning and attention, and small effects on working memory and spatial mapping - Mark D. Lindner; John B. Hogan; Donald B. Hodges; Anitra F. Orie; Ping Chen; Jason A. Corsa; John E. Leet; Kevin W. Gillman; Gregory M. Rose; Kelli M. Jones; Valentin K. Gribkoff (Psychopharmacology, 2006)

Short timescale air-sea coupling in the tropical deep convective regime - S. Gao; F. Ping; X. Cui; X. Li (Meteorology and Atmospheric Physics, 2006)

EU-OSTID: A Collection of Transposon Insertional Mutants for Functional Genomics in Rice - L. J. G van Enckevort; Gaëtan Droc; Pietro Piffanelli; Raffaella Greco; Cyril Gagneur; Christele Weber; Víctor M. González; Pere Cabot; Fabio Fornara; Stefano Berri; Berta Miro; Ping Lan; et al. (Plant Molecular Biology, 2005)

Cytosolic glucocorticoid receptor expression in the rat vestibular nucleus and hippocampus following unilateral vestibular deafferentation - Libby Lindsay; Ping Liu; Catherine Gliddon; Yiwen Zheng; Paul F. Smith; Cynthia L. Darlington (Experimental Brain Research, 2005)

The nature of spatial transitions in the Arctic - H. E. Epstein; J. Beringer; W. A. Gould; A. H. Lloyd; C. D. Thompson; F. S. Chapin; G. J. Michaelson; C. L. Ping; T. S. Rupp; D. A. Walker (Journal of Biogeography, 2004)
Aim Describe the spatial and temporal properties of transitions in the Arctic and develop a conceptual understanding of the nature of these spatial transitions in the face of directional environmental change. Location Arctic tundra ecosystems of the North Slope of Alaska and the tundra‐forest region of the Seward Peninsula, Alaska Methods We synthesize information from numerous studies on tundra and treeline ecosystems in an effort to document the spatial changes that occur across four arctic transitions. These transitions are: (i) the transition between High‐Arctic and Low‐Arctic systems, (ii) the transition between moist non‐acidic tundra (MNT) and moist acidic tundra (MAT, also referred to as tussock tundra), (iii) the transition between tussock tundra and shrub tundra, (iv) the transition between tundra and forested systems. By documenting the nature of these spatial transitions, in terms of their environmental controls and vegetation patterns, we develop a conceptual model of temporal dynamics of arctic ecotones in response to environmental change. Results Our observations suggest that each transition is sensitive to a unique combination of controlling factors. The transition between High and Low Arctic is sensitive primarily to climate, whereas the MNT/MAT transition is also controlled by soil parent material, permafrost and hydrology. The tussock/shrub tundra transition appears to be responsive to several factors, including climate, topography and hydrology. Finally, the tundra/forest boundary responds primarily to climate and to climatically associated changes in permafrost. There were also important differences in the demography and distribution of the dominant plant species across the four vegetation transitions. The shrubs that characterize the tussock/shrub transition can achieve dominance potentially within a decade, whereas spruce trees often require several decades to centuries to achieve dominance within tundra, and Sphagnum moss colonization of non‐acidic sites at the MNT/MAT boundary may require centuries to millennia of soil development. Main conclusions We suggest that vegetation will respond most rapidly to climatic change when (i) the vegetation transition correlates more strongly with climate than with other environmental variables, (ii) dominant species exhibit gradual changes in abundance across spatial transitions, and/or (iii) the dominant species have demographic properties that allow rapid increases in abundance following climatic shifts. All three of these properties characterize the transition between tussock tundra and low shrub tundra. It is therefore not surprising that of the four transitions studied this is the one that appears to be responding most rapidly to climatic warming.

Behavioral Response of Two Subterranean Termites (Isoptera: Rhinotermitidae) to Vibrational Stimuli - Xing Ping Hu; Arthur G. Appel; James F. A. Traniello (Journal of Insect Behavior, 2003)

Modelling carbon balances of coastal arctic tundra under changing climate - Robert F. Grant; Walter C. Oechel; Chien‐Lu Ping (Global Change Biology, 2003)
Rising air temperatures are believed to be hastening heterotrophic respiration (R h ) in arctic tundra ecosystems, which could lead to substantial losses of soil carbon (C). In order to improve confidence in predicting the likelihood of such loss, the comprehensive ecosystem model ecosys was first tested with carbon dioxide (CO 2 ) fluxes measured over a tundra soil in a growth chamber under various temperatures and soil‐water contents (θ). The model was then tested with CO 2 and energy fluxes measured over a coastal arctic tundra near Barrow, Alaska, under a range of weather conditions during 1998–1999. A rise in growth chamber temperature from 7 to 15 °C caused large, but commensurate, rises in respiration and CO 2 fixation, and so no significant effect on net CO 2 exchange was modelled or measured. An increase in growth chamber θ from field capacity to saturation caused substantial reductions in respiration but not in CO 2 fixation, and so an increase in net CO 2 exchange was modelled and measured. Long daylengths over the coastal tundra at Barrow caused an almost continuous C sink to be modelled and measured during most of July (2–4 g C m −2 d −1 ), but shortening daylengths and declining air temperatures caused a C source to be modelled and measured by early September (∼1 g C m −2 d −1 ). At an annual time scale, the coastal tundra was modelled to be a small C sink (4 g C m −2 y −1 ) during 1998 when average air temperatures were 4 °C above normal, and a larger C sink (16 g C m −2 y −1 ) during 1999 when air temperatures were close to long‐term normals. During 100 years under rising atmospheric CO 2 concentration (C a ), air temperature and precipitation driven by the IS92a emissions scenario, modelled R h rose commensurately with net primary productivity (NPP) under both current and elevated rates of atmospheric nitrogen (N) deposition, so that changes in soil C remained small. However, methane (CH 4 ) emissions were predicted to rise substantially in coastal tundra with IS92a‐driven climate change (from ∼20 to ∼40 g C m −2 y −1 ), causing a substantial increase in the emission of CO 2 equivalents. If the rate of temperature increase hypothesized in the IS92a emissions scenario had been raised by 50%, substantial losses of soil C (∼1 kg C m −2 ) would have been modelled after 100 years, including additional emissions of CH 4 .

Radioiodinated styrylbenzene derivatives as potential SPECT imaging agents for amyloid plaque detection in alzheimer’s disease - Mei-Ping Kung; Catherine Hou; Zhi-Ping Zhuang; Daniel M. Skovronsky; Bin Zhang; Tamar L. Gur; John Q. Trojanowski; Virginia M. -Y. Lee; Hank F. Kung (Journal of Molecular Neuroscience, 2002)

The activation state of Rubisco directly limits photosynthesis at low CO2 and low O2 partial pressures - Rowan F. Sage; Yan-Ping Cen; Meirong Li (Photosynthesis Research, 2002)

Mammary fibroblasts stimulate growth, alveolar morphogenesis, and functional differentiation of normal rat mammary epithelial cells - Kathleen M. Darcy; Danilo Zangani; Wendy Shea-Eaton; Suzanne F. Shoemaker; Ping-Ping H. Lee; Lawrence H. Mead; Anuradha Mudipalli; Roberta Megan; Margot M. Ip (In Vitro Cellular & Developmental Biology - Animal, 2000)

Localization of occludin, ZO-1, and pan-cadherin in rabbit ciliary epithelium and iris vascular endothelium - Ping Wu; Haiyan Gong; Rozanne Richman; Thomas F. Freddo (Histochemistry and Cell Biology, 2000)

MAMMARY FIBROBLASTS STIMULATE GROWTH, ALVEOLAR MORPHOGENESIS, AND FUNCTIONAL DIFFERENTIATION OF NORMAL RAT MAMMARY EPITHELIAL CELLS - KATHLEEN M. DARCY; DANILO ZANGANI; WENDY SHEA-EATON; SUZANNE F. SHOEMAKER; PING-PING H. LEE; LAWRENCE H. MEAD; ANURADHA MUDIPALLI; ROBERTA MEGAN; MARGOT M. IP (In Vitro Cellular & Developmental Biology - Animal, 2000)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)

Functional studies on the anti-pathoangiogenic properties of CM101 - He-Ping Yan; Clint E. Carter; En-ze Wang; David L. Page; Kay Washington; Barbara D. Wamil; F. Michael Yakes; Gary B. Thurman; Carl G. Hellerqvist (Angiogenesis, 1998)

The β 2 -agonist salbutamol affects the expression of phospholamban and both isoforms of SERCA in canine skeletal muscle and blocks changes in these induced by neuromuscular stimulation - K.-M. Zhang; Ping Hu; Shang-Wu Wang; Leon D. Wright; Andrew S. Wechsler; John A. Spratt; F. N. Briggs (Pflügers Archiv - European Journal of Physiology, 1998)

Correlations between MyoD, myogenin, SERCA1, SERCA2 and phospholamban transcripts during transformation of type-II to type-I skeletal muscle fibers - Ping Hu; K.-M. Zhang; Leon D. Wright; John A. Spratt; F. N. Briggs (Pflügers Archiv - European Journal of Physiology, 1997)

Fast- and slow-twitch isoforms (SERCA1 and SERCA2a) of sarcoplasmic reticulum Ca-ATPase are expressed simultaneously in chronically stimulated muscle fibers - K.-M. Zhang; Ping Hu; Shang-Wu Wang; Leon D. Wright; Andrew S. Wechsler; John A. Spratt; F. N. Briggs (Pflügers Archiv - European Journal of Physiology, 1997)

Induction of molecular and mechanical transformations in canine skeletal muscle by chronic neuromuscular stimulation - KE- MIN ZHANG; LEON D. WRIGHT; PING HU; JOHN A. SPRATT; ANDREW S. WECHSLER; F. NORMAN BRIGGS (Journal of Muscle Research and Cell Motility, 1997)